Developing a Forestry Business Model Through the Business Model Canvas: A Case Study in Gerlang Village, Batang Regency, Central Java - Setyadi, Anggy Riskha Putri; Purnomo, Heri; Trison, Soni (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
At the local level, social forestry is a key strategy for implementing sustainable forest management that aims to reduce poverty, empower local communities, and improve forest conditions. Granting forest area management permits to local communities requires good business development planning. This study used the business model canvas framework to develop a new business model. The result showed that a new business model was developed by considering the benefits of vegetables, arabica coffee, and tree carbon storage as the value propositions. The customer segments were housewives, restaurant owners, coffee shop owners, and CO2-emitting companies. The products were distributed through trader networks and voluntary carbon market mechanisms. Farmers established direct relationships with trader networks. Revenue streams were derived from the sales of fresh potatoes, carrots, leeks, chilies, coffee beans, and carbon credits. This business model required an area, irrigation equipment, farming equipment, seeds, fertilizers, laborers, and tree biomass measuring tools. Key activities included farming, measurement, and calculation of carbon storage estimates. The partners in this business model were community organisations and local government agencies. The cost structures were investment, operational farming, and costs associated with measuring and calculating carbon storage.